Correction: Zhang et al. Genome-Scale CRISPR Knockout Screening Identifies BACH1 as a Key Regulator of Aflatoxin B1-Induced Oxidative Damage. Antioxidants 2022, 11, 1787 - Jinfu Zhang; Siyi Hu; Changzhi Zhao; Yuan Zhou; Lu Zhang; Hailong Liu; Peng Zhou; Sheng Li; Liangliang Fu; Zhuqing Zheng; Yue Xiang; Xuewen Xu; et al. (MDPI AG, 2023)
In the original publication [...]